Production of Healthy Protein and Snack Foods for Small-scale Industry from Full Fat Soy Flour - Chulaluck Charunuch; Kritsana Temtrakool; Saovaluk Runggaeng; Urai Paosungthong; Warunee Varanyanond (Agriculture and Natural Resources, 2006)
A village texturizer has been developed in this study to produce healthy protein and snack food products from full fat soy flour. Owing to its uncomplicated technology, lower operating and maintenance costs, this machine could be used effectively at its optimum pressure and temperature to produce food products for small–scale industry. Full fat soy flour was produced with low heat treatment and used as a raw material in the production of healthy protein and snack foods. For protein food, the production conditions were varied as: full fat soy flour:sesame residue of 100:0, 90:10; temperature of 180, 200, 220 oC; pressure of 5 and 7 bar. On the other hand, the production conditions for snack foods were varied as: full fat soy flour:tapioca flour of 20:80, 30:70; temperature of 150 , 170 oC; pressure of 3, 5 and 7 bar . The products were then evaluated in terms of appearance, water holding capacity (only protein food), texture (hardness and chewiness / crispiness) and sensorial quality. The results showed that the production of protein food should be conducted using high full fat soy flour (100%), suitable pressure (5 bar) and not too high temperature (180oC) in order to get the best product with good shape, colour and texture. In contrast, the production of snack food should be conducted using low full fat soy flour (20%), low temperatme (150oC) and high pressure (7 bar) to get the smooth circular shape and good color with high expansion. Furthermore, both finished products were evaluated in terms of the nutrition labeling, which was fitted for protein and snack foods.